Male Sex Work in the Digital Age Curated Lives - Ryan, Paul (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores the lives of male sex workers living in Dublin, Ireland. It focuses on the stories of young Brazilian and Venezuelan migrants who use their micro-celebrity on social media to construct a brand that can be converted into financial advantage within the sex industry. The book focuses on two sites: Grindr, which these men use to build a transient pop-up escort profile that is linked to Instagram, which in turn provides followers with access to a curated digital identity built around consumption. Ryan explores how the muscular body acts as a form of physical and erotic capital providing the raw material of these digital identities as they are broadcast on new online subscription platforms like OnlyFans. Male Sex Work in the Digital Age offers fascinating insights into the role social media plays in (re)creating a new and more flexible understanding of commercial sex. Students and scholars across a range of disciplines, including sociology, gender studies, sexuality studies, LGBTQ studies, media studies and law, will find this book of interest. .